Eosinophilic gastrointestinal disorders - Karwowska, Anna; Nowicki, Wojciech; Zowczak, Agata; Wojno, Aleksandra; Kempiński, Radosław (Alergologia Polska - Polish Journal of Allergology, 2026)
Primary eosinophilic gastrointestinal disorders involve eosinophil infiltration in the gastrointestinal tract without other known causes of tissue eosinophilia. These include eosinophilic esophagitis, the most common form, and eosinophilic gastritis, enteritis, and colitis, typically of allergic origin. Eosinophilic esophagitis is a chronic Th2 inflammatory disease affecting esophageal function, causing heartburn, regurgitation, dysphagia, and abdominal pain. Previously rare, eosinophilic esophagitis now affects about 4 in every 10,000 individuals, mainly males. Eosinophilic esophagitis is triggered by food and environmental allergens. In adults, it causes dysphagia and chest pain; in children, feeding difficulties and regurgitation. Diagnosis requires endoscopy and biopsy with at least 15 eosinophils per high-power field, excluding other causes. Treatment includes proton pump inhibitors, topical steroids, and dietary changes like elimination diets. Sometimes, esophageal dilation is needed. Eosinophilic gastroenteritis and eosinophilic colitis are less common, affecting the stomach, small intestine, or colon, causing pain, diarrhea, and weight loss. Management involves glucocorticoids and dietary modifications. Ongoing research aims to improve diagnostics and treatments, focusing on targeted therapies to enhance patients’ quality of life.